Polemik Pilkada 2020 Di Masa Pandemi Covid-19: Antara Demokrasi Dan Oligarki - Muhlis Muhlis (Jayapangus Press, 2021)
This research aims to gather differences of opinion in responding to the 2020 Regional Head Elections (Pilkada) during the Covid-19 pandemic which has been determined through the decision of Government Regulation in Lieu of Law (Perppu) No. 2 of 2020. The 2020 Pilkada polemic that occurs in the community is, (1) the implementation of the 2020 Pilkada allows the opportunity for the transmission of Covid-19 at each stage of the election, (2) democracy places Pilkada as an important mandate in Law No. 10 of 2016 Article 201 Paragraph 6, meanwhile (3) the allegation of oligarchic politics is getting stronger in the 2020 Pilkada event during the Covid-19 pandemic. The 2020 election polemic in the community has been compiled with a systematic analysis of the literature to collect, process, and conclude data according to the target being reviewed, using qualitative descriptive techniques. So as to produce the following discussion: (1) Projection of the 2020 regional elections in the midst of the Covid-19 pandemic, is the duty, authority and responsibility of the KPU. (2) The 2020 Pilkada will continue to be held as a form of consistency of democracy during the Covid-19 pandemic. (3) Pilkada 2020 during the Covid-19 pandemic and the strengthening of oligarchic politics. The conclusion of the polemic that occurred, apart from the pros and cons of holding the 2020 Pilkada, is a form of evaluation and a democratic process that is equally sympathetic to the development of democracy and the creation of constitutional legal sovereignty of the Indonesian people